Proposition of an action layer for electrum - Brunel, Julien (2018)
Electrum is an extension of Alloy that adds (1) mutable signatures and fields to the modeling layer; and (2) connectives from linear temporal logic (with past) and primed variables à la TLA+ to the constraint language. The analysis of models can then be translated into a SAT-based bounded model-checking problem, or to an LTL-based unbounded model-checking problem. Electrum has proved to be useful to model and verify dynamic systems with rich configurations. However, when specifying events, the tedious and sometimes error-prone handling of traces and frame conditions (similarly as in Alloy) remained necessary. In this paper, we introduce an extension of Electrum with a so-called “action” layer that addresses these questions.